2022
DOI: 10.1002/htj.22559
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of heat and mass transport by double‐diffusive magnetoconvection in an electrically conducting fluid under sinusoidal/non‐sinusoidal rotational modulation

Abstract: In this paper, we study the effects of rotational modulation on heat and mass transport due to double-diffusive magnetoconvection in an electrically conducting fluid. In the study, different modes of rotational modulation are considered. Using a perturbation method, a Ginzburg-Landau equation which is nonautonomous is obtained for the modulation amplitude. The effect of rotational modulation on the heat and mass transfer is studied. For the investigation of the effect of buoyancy ratio on the onset of convecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…They observed that the waviness of the lower surface of the cabinet could enhance the Nusselt number. Similar studies are available in the literature (Biswas et al, 2022;Hamzah et al, 2022;Cho, 2019;Hussain et al, 2017;Rudziva et al, 2022;.…”
Section: Introductionsupporting
confidence: 66%
“…They observed that the waviness of the lower surface of the cabinet could enhance the Nusselt number. Similar studies are available in the literature (Biswas et al, 2022;Hamzah et al, 2022;Cho, 2019;Hussain et al, 2017;Rudziva et al, 2022;.…”
Section: Introductionsupporting
confidence: 66%
“…To name a few, oceanography, magma chambers, solar ponds, solidification of alloys, cooling towers, drying technologies, solar collector, pin-fin devices, insulation of nuclear reactor, solar plate collector, cooling process of electronic devices, and so forth. [1][2][3][4][5][6][7][8][9][10] On the other hand, the deviation from the idealized conditions (i.e., uniform temperature and concentration) is quite frequently found in the pragmatic conditions. Therefore, an in-depth study of heat and mass transfer (HMT) characteristics in such systems subjected to nonuniform heating and concentration conditions is of prime essence.…”
Section: Introductionmentioning
confidence: 99%
“…DDC has all‐embracing findings in different natural and man‐made activities. To name a few, oceanography, magma chambers, solar ponds, solidification of alloys, cooling towers, drying technologies, solar collector, pin‐fin devices, insulation of nuclear reactor, solar plate collector, cooling process of electronic devices, and so forth 1–10 . On the other hand, the deviation from the idealized conditions (i.e., uniform temperature and concentration) is quite frequently found in the pragmatic conditions.…”
Section: Introductionmentioning
confidence: 99%